PENERAPAN PENDEKATAN STRUKTURAL THINK-PAIR -SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR DAN AKTIVITAS SlSWA KELAS 1.7 SLTPN 20 PEKANBARU PADA POKOK BAHASAN KEANEKARAGAMAN HEWAN TA. 2002/2003 - Rosmaini S; Evi Suryawati; Mariani N. L (Program Studi Pendidikan Biologi, 2004)
This research was to know the increase of result learn and class student activity at SLTP 20 Pekanbaru, in Januari-March 2003. Samples were collected amount to 42 people, with measured parameter cover result learn by test and activity student with observation. Data analysis was conducted by descriptive. The result of research indicate that approach of Think-Pair-Share can improve result learn and student activity at chapter animal diversity. Where average result of learning to range from 67,26 until 81,85 with result of test 74,85. The activity student was indicate goodness with average 69,27%. Ke words : Think-Pair-Share, student learning, activity